The Function, Space, Form and Meaning of the Traditional House of Tolaki Tribe in Konawe, Southeast Sulawesi - Nidia Islamiah; Ria Wikantari; Asniawaty Kusno (EPI International Journal of Engineering, 2021)
The architecture of traditional house of the Tolaki tribe has characteristics that indicate the activities, identity and socio-cultural values of the community. This study aims to examine the function, space, form, and meaning of the traditional house of the Tolaki tribe. Field surveys were conducted at Meluhu Village in Meluhu District and Asambu Village in Unaaha District of Konawe Regency. This research is qualitative with phenomenological method. Data were collected through field observations, in-depth interviews, and document studies. The objects of research were is Laika Mbuu and Laika Aha houses which were selected from nine forms of Laika in Konawe Regency using purposive-criteria sampling technique. Data were analyzed descriptively, then the results were discussed and associated with relevant theories. The result reveals that the function of Laika Mbuu and Laika Aha is formerly the residence a Mokole (King) and a place to hold traditional ceremonies. However nowadays Laika Mbuu has become a communal gathering place and other public purposes, whereas Laika Aha become a customary house for ceremonial events. The spatial arrangement of Laika Mbuu has no partition so that the local community carries out all activities in one open space, whereas Laika Aha contains partitions that divide the space into several rooms. Both the Laika Mbuu and Laika Aha have a rectangular building shape. The square shape on the building facade shows a bottom container called Kalo Sara, which is a set of objects as symbol of social class and has a meaning as customary law in the Tolaki community. This research concludes that both the Laika Mbuu and Laika Aha have similar function and form, however different spatial arrangement. Both the Laikas express many symbolic meanings, among others that the house as symbol of a human body, and the residents symbolize organs of the human body, so that once the house is built and filled, it must try to protect itself from all obstacles and calamities.